Temporary Urban Projects: Proposing a Multi-Positional Framework for Critical Discussion - Skytt-Larsen, Christine Benna; Busck, Anne Gravsholt; Lamm, Bettina; Wagner, Anne Margrethe (Frontiers in Sustainable Cities, 2022)
The aim of this article is to create fertile ground for critical discussion of the discursive field of temporary urban projects (TUPs), their multiple positionings and governance potential in urban and metropolitan development. TUPs constitute short-lived or temporally restricted spatial interventions and social activities in otherwise vacant urban settings. Often made from cheap materials and simple construction methods, TUPs activate urban spaces in transition. Through spatial appropriations, TUPs can explore new uses and potentials in these transforming urban areas. Despite aesthetic and spatial similarities, the discursive field of TUPs is diverse and covers a plethora of uses and understandings of space, actors, activities, intentions and strategies. A critical discussion that recognizes the multiple positionings of the discursive field of TUPs can deepen and nuance our understanding of the governance potential of TUPs contributing to metropolitan urban development. Because of the diversity in actors, strategies and impacts of TUPs and thus, variations in rationales and positions, we suggest that the phenomenon of TUPs to be perceived as a new urban genre that can be approached from several interrelated perspectives reflecting a diverse discursive field with multiple positionings: (1) a spatial-architectural perspective; (2) an urban-economic perspective; (3) a socio-cultural perspective; (4) a local-social perspective; and (5) a political-planning perspective. This multifaceted and critical approach mirrors the different discursive positionings, initiating rationales, and accompanying practices of TUPs and helps us comprehend and critically discuss the governance perspectives that TUPs bring into the design and planning of urban and metropolitan regions.